Qualitative Research Methods: An essay review - McLean, Les; Myers, Margaret; Smillie, Carol; Vaillancourt, Dale (Education Policy Analysis Archives, 1997)
Miller, Steven I. & Fredericks, Marcel (1994) Qualitative Research Methods: Social Epistemology and Practical Inquiry. New York: Peter Lang. 159 pages.